SAMPLE-A RAW DATA FOR FUTURE INFORMATION OF LIFE - AISHWARYA, A.; SELVAM, VIJAYKUMAR; NANCY, A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2019)
Gene amplification requires a biological sample which is collected prior to the demands. The sample for such analysis plays a vital role as they serve as a resource for the core material-Deoxyribonucleic acid. A sample for gene amplification or any analysis would be collected prior to the demands and type of analysis. Human blood has been an essential resource of DNA from the commencement of DNA extraction in the 19th century. After then several protocols developed according to the requirement of both samples of different forms and their retrieval as various forms and methods. The sample has various characteristics and prerequisites when collected for gene analysis. Some important characteristics of sample collection methods are significant, which are not widely taken. This work analyses various general sample collection protocols and highlights some of the major characteristics and prerequisites for the sample. This work initiates and delivers to attain the core of genomics by bringing out the basic raw materials importance and consequences on amplification which is highly sensitive.